Respons pertumbuhan dan hasil tanaman kedelai hitam (Glycine max (L) Merril) terhadap berbagai konsentrasi biourine dan pupuk KCl - Chindy Charin Marlisa; Samsul Bahri; Sutedjo Sutejo (Composite : Jurnal Ilmu Pertanian, 2024)
This research aims to study the response of growth and yield of black soybean plants to various concentrations of biourine and KCl fertilizer. Soybean (Glycine max (L) Merril) has a high anthocyanin content so it is good for people with diabetes mellitus, besides that it has a protein content of 45.58% and 14.83% fat. The need for soybeans has increased every year, therefore land utilization and the provision of biourine fertilizer and KCl fertilizer is one of the efforts to increase soybean production in order to meet the increasing consumption needs. The research was conducted from October-December 2021 located in Terawas Village, STL ULU Terawas District, Musi Rawas Regency, South Sumatra Province. The design used Factorial Randomized Group Design (RAK) with two factors, the first factor is biourine fertilizer and the second factor is KCl fertilizer. There are 16 treatment combinations were obtained, repeated 3 times, and each treatment consisted of 2 polybags so that 96 polybags were obtained. The observed variables include plant height, number of branches, number of pods, weight of seeds per plant, weight of 100 seeds per plant. Analyzed using ANOVA (5%) and continued with further BNT 5%. The results showed that the treatment of B3 dose of 300 mL/L water and K3 dose of 230 kg/ha was able to produce the best growth in black soybean plants. In the treatment interaction (B3K3) produces the best growth and production in black soybean plants showing a linear response to the dose of bioruine given, so that the optimal dose cannot be determined, the highest results are achieved at the highest dose.